Implant Complications in 20 Triple Pelvic Osteotomies - Remedios, Audrey M.; Fries, Cindy L. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
In 12 dogs with hip dysplasia, 20 triple pelvic osteotomies (eight bilateral and four unilateral) were performed. Screw loosening, occurring in six of 12 dogs (seven of 20 osteotomies), was the most common complication after surgery. Implants loosened from the cranial ilium in six hemipelvises (30%) and from both fragments in one hemipelvis, two to six weeks (mean — three) after the operation. Medial acetabular displace-ment caused pelvic narrowing (6 to 9%, mean = 8%) in three of four dogs. Medial ischial displacement decreased pelvic diameter (11 to 21%, mean = 17%) in four of seven osteotomies. All of the dogs with implant failure were treated conservatively with cage rest and in two cases Ehmer slings were used. Although none were lame, gait abnormalities were evident in three of seven dogs on follow-up examinations four to 12 months (mean = six) later.Screw loosening, occurring in seven of 20 hemipelvises, was the most common postoperative complication associated with triple pelvic osteotomy. Fixation failures were managed conservatively. Despite decreased pelvic diameter in four of seven animals, none were lame or showed signs of pelvic obstruction at follow-up examinations four to 12 months later.
Keywords: Hip dysplasia; triple pelvic osteotomy; implant loosening